HUBUNGAN PEMBERIAN MOTIVASI OLEH GURU PENDIDIKAN AGAMA KRISTEN DENGAN HASIL BELAJAR SISWA KELAS XI SMA SWASTA HKBP 2 TARUTUNG TAHUN PEMBELAJARAN 2017/2018 - duma simatupang (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
vAbstract, This research is purposed to know the relationship of the motivation giving by The Christian RelegionEducation Teacher with The Study Result of The XI Grade Students at SMA Swasta HKBP 2 Tarutung StudyYear 2017/2018. The Hypotheses of this resarch : Is found the positive anf significant relationship between ofthe motivation giving by The Christian Relegion Education Teacher with The Study Result of The XI GradeStudents at SMA Swasta HKBP 2 Tarutung Study Year 2017/2018. This research is the correlation researchwhich is used the descriptive and inferensial statistic technic. The populations are all of the XI Grade Studentsat SMA Swasta HKBP 2 Tarutung Study Year 2018/2019 which are Cristian as much 113 persons. The samplesis determined by random sampling as 45% from the populations is 52 persons. The instrument of the research isclosed inquiry. The result of the value anlysis for rxy=0,484ttable=0,29 shows that there is the relationshipbetween the motivation giving by The Christian Relegion Education Teacher with The Study Result of The XIGrade Students at SMA Swasta HKBP 2 Tarutung Study Year 2017/2018 with the medium category. From testof the hypotheses is got tcount=3,911ttable=2,021 so the H0 is refused and the Ha is received.Keywords : Motivation The Teacher, Study Result